Credit rating downgrade risk on equity returns - Periklis Brakatsoulas; Jiri Kukacka (Charles University in Prague, Institute of Economic Studies (IES), 2020)
We develop a four-factor model intended to capture size, value, and credit rating transition patterns in excess returns for a panel of predominantly mid- and large-cap entities. Using credit transition matrices and rating histories from 48 US issuers, we provide evidence to support a statistically significant negative downgrade risk premium in excess returns, suggesting that stocks at higher risk of failure tend to deliver lower returns. The performance of the model remains robust across several estimation methods. Panel Granger causality test results indicate that there indeed is a Granger-causal relationship from credit rating transition probabilities to excess returns. Our paper thus provides a new methodology to generate firm-level downgrade probabilities and the basis for further empirical validation and development of Fama-French-type models under financial distress.
Keywords: G11; G12; G14; G41; 330; Asset pricing; credit risk; panel data; stock returns; transition matrices